Microbial Profile and Antibiotic Sensitivity Patterns in Infectious Keratitis - Muhammad Bilal, Shafqat Ali Shah, Muhammad Tariq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Infectious Keratitis is a vision-threatening eye emergency which needs timely etiological diagnosis and relevant antimicrobial treatment. Patterns of antibiotic resistance and causative organisms vary with geographical location and vary over time. Local surveillance is hence necessary periodically to inform empirical management approaches and minimise the chances of corneal scarring and permanent visual disability. Objective: The knowledge gained in the study is expected to provide the microbial profile of the infectious keratitis and the patterns of antibiotic sensitivity of the isolated organisms among patients who have consulted a tertiary-level ophthalmology unit. Methodology: The study was a cross-sectional study conducted at the Department of Ophthalmology unit BKMC Mardan from January 2022 to June 2022 which involved 100 patient subjects who were clinically diagnosed with infectious keratitis. The corneal scrapings were collected under the aseptic environment and analyzed with the help of Gram staining, potassium hydroxide mount, and culture in blood agar, chocolate agar, and Saburou dextrose agar. The Kirby-Bauer disc diffusion technique was used to determine the antibiotic susceptibility according to the Clinical and Laboratory Standards Institute guidelines. Data analysis was performed through SPSS version 24.0, whose data were represented in the form of frequencies and percentages. Conclusion: The dominant bacterial and fungal causes of infectious keratitis were Staphylococcus aureus and Aspergillus species, respectively. The sensitivity of isolates to vancomycin, fluoroquinolones, and natamycin is high and thus encourages further application in isolates as the first-line empirical treatment, as a result of which the regular use of microbiological assessment is essential to ensure the best patient outcome. Results: Positive cultures were obtained in 82% of cases. Bacterial pathogens constituted 65.9% of isolates, while fungal organisms accounted for 34.1%. Staphylococcus aureus was the most common bacterial isolate (28.0%), followed by Pseudomonas aeruginosa (21.0%) and Streptococcus pneumoniae (16.9%). Among fungal isolates, Aspergillus species (19.5%) were predominant, followed by Fusarium species (14.6%). Gram-positive bacteria showed the highest sensitivity to vancomycin (92.3%) and moxifloxacin (85.7%), whereas gram-negative isolates were most sensitive to ciprofloxacin (88.2%) and ceftazidime (82.3%). Fungal isolates demonstrated maximum susceptibility to natamycin (90.0%) and amphotericin-B (83.3%). Keywords: Infectious keratitis; microbial profile; antibiotic sensitivity; corneal ulcer; Pakistan.